Pentingnya Pendidikan Rohani bagi Anak dalam Keluarga di Era Disruptif - Susilo, David Priyo; Jon, Jon; Manik, Disetra Fiser; Rombe, Eni; Gidion, Gidion (Fakultas Ilmu Keguruan dan Pendidikan, Universitas Kristen Indonesia, 2022)
The disruptive era is marked by rapid changes in all areas of life. Technological developments and cultural changes certainly greatly affect children's lives. Pornography, bullying, fraud, shows of violence, rules, lack of ethics, individualism, and skepticism of religion/God are a few of the problems in this disruptive period. The health of a child's life is determined by the health of his spiritual life. The spiritual health of children must be intentional by optimizing spiritual education in the family. The purpose of this research is to build a spiritual education plan by parents for children in disruptive times and how to apply it according to the rules of the Christian faith. This study was constructed using a literature-qualitative study. Based on the results of the study, the spiritual education of children in the family that parents strive for has a very positive impact on the spiritual growth of children in disruptive times. AbstrakEra disruptif ditandai dengan perubahan yang pesat pada segala bidang kehidupan. Perkembangan teknologi dan perubahan budaya tentu sangat mempengaruhi kehidupan anak. Pornografi, perundungan, penipuan, tayangan kekerasan, tauran, minim etika, individualis, skpetis terhadap agama/Tuhan merupakan segelitir masalah di masa disruptif ini. Sehatnya kehidupan anak ditentukan oleh sehatnya kehidupan rohaninya. Kesehatan kerohanian anak harus disengaja dengan cara mengoptimalkan pendidikan kerohanian dalam keluarga. Tujuan penelitian ini adalah untuk membangun sebuah rancangan pendidikan kerohanian oleh orang tua bagi anak-anak di masa disruptif dan bagaimana menerapkannya sesuai kaidah iman Kristen. Penelitian ini dikonstruksi menggunakan kajian literatur-kualitatif. Berdasarkan hasil penelitian maka pendidikan rohani anak dalam keluarga yang diupayakan orang tua sangat berdampak positif kepada pertumbuhan kerohanian anak di masa disruptif.